Sport management principles and applications - Hoye, Russell; Misener, Katie; Ordway, Catherine; Hoye, Russell 1966-; Naraine, Michael L. 1987- (Sport Management Series, 2022)
"Now available in a fully revised and updated sixth edition, Sport Management: Principles and Applications tells you everything you need to know about the contemporary sport industry. Covering both the professional and nonprofit sectors, and with more international material than any other introductory sport management textbook, it focuses on core management principles and their application in a sporting context, highlighting the unique challenges of a career in sport management. The book contains useful features throughout, including conceptual overviews, guides to further reading, links to important websites, study questions, and up-to-date case studies showing how theory works in the real world.